Control of Dispersion of Agglomerated Particles in Water by Electrostatic Repulsion Force [Translated]† - Yasuo Kousaka; Yoshiyuki Endo; Takahiro Horiuchi; Yoshiyuki Sasaki (KONA Powder and Particle Journal, 2014)
The effect of electrostatic repulsion force arising from the surface potential ψ and the double layer I/χ around a particle on dispersion or de-agglomeration of agglomerated particles in water is discussed. Several suspensions of PSL (polystyrene latex) particles in an agglomerated state where Ψ and 1/χ are respectively controlled by the pH and the electrolyte concentration Ce were prepared. They were accelerated in a convergent nozzle to give an external force on particles and agglomerated particles were dispersed into primary particles. PSL particles thus dispersed were observed with an optical microscope. It was found that the dispersion of agglomerated particles were enhanced with an increase of Ψ and Ce under a constant external force or a constant flow rate in the nozzle. It is well understood that the dispersion of particles with higher surface potential ψ is much easier. It is, however, intuitively curious that the dispersion of agglomerated particles in higher electrolyte concentration Ce is much easier, since coagulation is usually enhanced in such a higher Ce suspension. The experimental results may be applied to control the dispersion of agglomerated particles in water.† This report was originally printed in KAGAKU KOGAKU RONBUNSHU 21(2), 372-377 (1995) in Japanese, before being translated into English by KONA Editorial Committee with the permission of the editorial committee of the Soc. Chemical Engineers, Japan.